PENINGKATAN KOMPETENSI BAHASA INGGRIS DAN LITERASI SISWA SMAN 1 PULE TRENGGALEK MELALUI PELATIHAN “HOW TO SPEAK ENGLISH CONFIDENTLY” - Susanto Susanto; Fahrudin Fahrudin; Yahmun Yahmun (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
English training Confidence is the key of success in education. Armed with confidence, every student could certainly develop into a human with a good character. Student who are confident will be able to accept himself, ready to accept the challenge in the sense of want to try something new even though aware that the possibility of one must have and tend to be more successful in doing what he want. The objective of this community service activity is to provide scientific assistance to the students of SMAN 1 Pule Trenggalek in learning English, especially how to speak English confidently. The community service activity was carried out in the form of short training with members of 40 students held in the hall of SMAN 1 Pule Trenggalek. The method used in this community service activity is lecturing, drilling, questioning and practicing. Based on observation during this community service activity, several results were obtained. The results of this community service activity are increased insight of students of SMAN 1 Pule Trenggalek on speaking English confidently. The students in SMAN 1 Pule Trenggalek can speak fluently, dare to ask and declare in front of the class.